Urine Stimulation Activates BK Channels in Mouse Vomeronasal Neurons - Zhang, Peng (American Physiological Society, 2008)
Most odor responses in mouse vomeronasal neurons are mediated by the phospholipase C (PLC) pathway, activation of which elevates diacylglycerol (DAG). Lucas et al. showed that DAG activates transient receptor potential channels, subfamily C, member 2 (TRPC2), resulting in a depolarizing Ca(2+) influx. DAG can be subsequently converted to arachidonic acid (AA) by a DAG lipase, the role of which remains largely unknown. In this study, we found that urine stimulation of vomeronasal neurons activated large-conductance Ca(2+)-activated K(+) (BK) channels via AA production. Using isolated neurons, we demonstrated that repetitive applications of AA potentiated a K(+) current that required a Ca(2+) influx and was sensitive to specific BK blockers. Using immunocytochemistry, we found that BK channels are present in vomeronasal neurons with labeling on the soma and heavy labeling on the dendrite with a BK channel antibody. We examined the role of these BK channels in regulating neuronal firing when the neuron was activated by membrane depolarization or urine. Contrary to a recent report, our data suggest that BK channels contribute to adaptation of urine/odor responses because the inhibition of BK channels during urine stimulation promoted repetitive firing. These data strongly support the hypothesis that AA mediates an inhibitory pathway through BK channels, a possible mechanism for odor adaptation in vomeronasal neurons.